Model organizacji uczącej się jako propozycja dla bibliotek akademickich = A model of a learning organization as a proposal for academic libraries - Adaszyńska, Ewa (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
The changing environment in which the organisation functions requires adjustments in the management models. The solution is supplied by the concept of learning organisation which is able to operate in the unstable environment and adjust to changes, as well as to use the possibilities of development and sustainability. The pursuit of continuous learning, better use of knowledge as well as new solutions and innovations in both the organization itself and its surroundings of the organisation and its environment, change the conditions of its functioning and introduce a new way of thinking according to which the effectiveness and efficiency, development and success of the organisation should be considered in terms of responsibilities and results. For the learning organisation the most important are the acquisition of intellectual capital and the management of knowledge supporting the acquisition, the analysis and application of knowledge aiming at better decision making and implementation of current and perspective goals and objectives. The immaterial resources - knowledge, intellectual capital, learning - are discussed in the current paper with an emphasis on their importance for the academic library aspiring to be a knowledge - based model of learning organisation.
Keywords: biblioteki; biblioteki akademickie; innowacje; kapitał intelektualny; organizacje; uczenie się; wiedza; zarządzanie wiedzą; libraries; academic libraries; innovations; intellectual capital; organizations; learning; knowledge; knowledge management